Emergent Trends in Nigeria’s Popular Entertainment: Cross-Dressing and Blurred Identity in Social Media Skits - Ben-Iheanacho, Elizabeth Onyewuchi; Gbenoba, Emefiele Felix; Husseini, Shaibu (The Journal of Society and Media, 2023)
This paper explores the relationship between mass media and its audience, specifically in Nigeria where this field is under-studied. Since its debut in 1959 as a medium of domestic entertainment, television in Nigeria has been a wonderland for new vistas and foreign and strange concepts that became trendsetters for viewers’ astonishment and enthusiastic lifestyle emulation. This study uses qualitative methods, including Key Informant Interviews and secondary analysis, to explore cross-dressing as a cultural phenomenon. The theoretical framework is based on the gratification and technological determinism theories. The study examines how technological advancements have enabled the normalization of "sophisticated, imported" options in entertainment culture. The paper explores gender fluidity and identity blurring in the artist's perception. The findings showed that the incursion of technology, especially television and its more sophisticated variant, social media, are the purveyors of democratized ideas of individual identity and blurred sexuality profiling that disrupted existentialist binary notions. The study results also showed that cross-dressing, as employed in skit-making, has earned respect on the employment index of the creative sector and art community. Tech shapes youth culture, paving the way for new norms in human relationships and personal expression